An Investigation of the Exercise Addiction of Sports and Social Life Center Members during the Covid-19 Pandemic Period - APAYDIN, Murat Bekleyiş; SİTTİ, Samet (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2022)
The present study aimed to determine the exercise addiction of the participants who actively attended the fitness centers within the sports and social life centers during the Covid-19 pandemic. In the study, the data were collected with the Exercise Addiction Scale and the obtained data were evaluated in the SPSS 22.0 statistical program. In the data analysis, first, the normality of the data was checked and the independent samples t-test and one-way analysis of variance tests were used. According to the results of the research, the average age of the participants was determined as (28.2±9.4 years). In addition, according to the findings obtained from the responses given to the scale items, the exercise addiction of the participants significantly differed according to the variables of gender and marital status, on the other hand, there was not any significant difference according to the variables of age and education level.